CADANGAN KEUANGAN NASIONAL SEBAGAI SUMBER DANA PEMBANGUNAN JANGKA PANJANG - Subianto, Ahmad (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
This paper discusses the policy of national financial reserves as a source of long-term development funds. The issue is whether a policy or strategy should be tailored to the identity of Indonesia with due regard to the prevailing generality or generally accepted business condition. How is the impact on poverty, employment and welfare of the citizens of the Nation. Very influential national financial reserve also to the welfare of society. Therefore, the establishment of a social security system program becomes necessary.